Moving more, ageing happy: findings from six low- and middle-income countries - Felez-Nobrega, Mireia (Age Ageing, 2020)
BACKGROUND: low levels of well-being (including happiness) in the older population are major global concern given rapid population ageing especially in low- and middle-income countries (LMICs). Physical activity may increase levels of happiness, but data on the older population are scarce, while there are no data from LMICs. OBJECTIVE: we investigated the relationship between physical activity and happiness, and the influential factors in this association among older adults employing nationally representative datasets from six LMICs. METHODS: community-based cross-sectional data from the Global Ageing and Adult Health study were analysed. Physical activity was assessed with the Global Physical Activity Questionnaire. Participants were grouped into those who do and do not meet physical activity recommendations. Happiness was assessed with a cross-culturally validated single-item question (range 0–4) with higher scores indicating higher levels of happiness. Multivariable ordinal logistic regression and mediation analyses were performed. RESULTS: the sample included 14,585 adults aged ≥65 years (mean age = 72.6 ± SD 11.4 years; 55% female). After adjusting for multiple confounders, meeting physical activity guidelines was positively associated with more happiness (fully adjusted model, odds ratio = 1.27; 95% confidence interval = 1.04–1.54). The physical activity–happiness association was largely explained by difficulties in mobility, cognitive impairment, disability and social cohesion, which explained ≥20% of the association. CONCLUSIONS: meeting recommended physical activity levels was positively linked with happiness in older adults from LMICs. Longitudinal and interventional studies among older people in LMICs are warranted to assess directionality and the potential for physical activity promotion to improve mental well-being in this population.